Pengembangan Model Pembelajaran PJOK Melalui Program SIBBER Untuk Meningkatkan Kebugaran Jasmani Berkarakter Sportivitas - Gholy, Muhammad Syarifuddin; Sumardi, Sumardi; Hadi, Santika Rentika (Journal of Sport Science and Education, 2021)
Learning model based on SHC (Students with Healthy Character is applied in Physical Sport and Health Education (PSHE), to present fun learning with the right target as the learning objectives of PSHE it self. The purpose of this development is to produce a SHC based PSHE learning Model Manual. This study uses a research design (Dick & Carey, 2015). Collecting qualitative data with triangulation techniques and quantitative with descriptive percentages. While the learning outcomes of tests and measurements as well as observations were analyzed using the paired t test using SPSS version 25. Based on the results of validation and product testing, it was obtained, 92.3% of learning design experts, 89.6% of PSHE material experts, and field of study educators. PSHE 95.1%, the results of the three validators, have met the criteria very well and do not need to be revised. While the results of the analysis of the small group trial was 75.50%, the large group was 88.30%. Furthermore, the results of learning physical fitness and sportsmanship character show the value of sig. 0.00<0.05.